Sosialisasi Modul Ajar Berbasis Culturally Responsive Teaching (CRT) Materi Luas Bangun Datar Kelas 5 Sekolah Dasar - Inka Fitriyani; Nabilla Athaya Munandar; Checilia Melita Sukmawati; Putri Zudhah Ferryka (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
Education is a very important part of human life. Through education, it is hoped that changes and developments will occur in human life over time. One effort that can be made to improve the quality of education and also increase cultural understanding is by using an approach that is very relevant to society, namely implementing culturally responsive teaching or culturally responsive learning. This approach requires teaching modules that will be used as the main instrument in the learning process. The implementation of teaching modules with culturally responsive teaching in the field itself still has several obstacles and challenges. So there is a need for socialization and assistance, especially for students as prospective educators to increase understanding of culturally responsive teaching-based teaching modules. The method used in this service is socialization.